Mother's Experience of Caring for Children with Stunting in the Riverside of Banjar Regency - Filia Sofiani Ikasari; Insana Maria; Chrisnawati; Fir’ad Setya Nugraha; Ahmad Rizqo Abdillah; Cut Ika Anugrah Kirana; Muhammad Wirandi (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Stunting is one of the most common impacts of chronic malnutrition in the world. Banjar Regency is one of the regencies in South Kalimantan that has experienced a significant increase in stunting cases. Mothers often act as the primary caregivers of children, thus all actions taken by mothers related to care including fulfilling nutritional needs can affect the health and nutritional status of their children. It is important for a mother to have good knowledge about fulfilling nutrition for children, fulfilling immunizations, maintaining sanitation and treating infectious diseases in children. One way to gain knowledge is from experience. Mothers with stunted children have experiences that can be lessons regarding the actions taken during treatment, the obstacles felt and how to prevent stunting in the next generation. Objective: This study aims to explore the experiences of mothers in caring for children with stunting in the riverside of ??Banjar Regency. Method: A qualitative approach with a phenomenological design was used in this study. Data were collected using the in-depth interview method and analyzed using the sequence: transcribing, categorizing, using N-Vivo 12. The population in this study were all mothers who had stunted children in the riverside of ??Banjar Regency. In this study, mothers who became participants were selected using a purposive sampling method, namely data was taken from information from health center officers in Banjar Regency with inclusion criteria having experience caring for children with stunting, being able to communicate well and being willing to be participants. Data saturation was obtained on the 16th participant. Result: The results of this study identified 5 themes, namely children's eating habits, children's conditions, mothers' efforts, mothers' difficulties and the role of fathers. Children's eating habits include incomplete menus, eating little, eating irregularly, eating without side dishes, and snacks before eating. The condition of stunted children in this study was slow development, frequent illness, and poor sleep quality. Mother’s efforts were to provide exclusive breastfeeding and routinely go to posyandu. The difficulties faced by mothers were difficulty in accessing health facilities, economic problems, children who did not want to be separated from their mothers, confusion in handling stunting and the presence of a closed mouth movement in children. The role of fathers included collaborating with mothers in parenting and being less involved in parenting. Conclusion: The conclusion obtained in this study was that 5 themes were obtained from the experience of mothers in caring for children with stunting in the riverside of Banjar Regency.